Optimization of larval culture for the production of juvenile spotted snapper Lutjanus guttatus in Costa Rica - Chacón-Guzmán, Jonathan (2021)
The technological foundation of the Lutjanus guttatus aquaculture was developed in Costa Rica in 2002 by Parque Marino del Pacífico. The first juvenile mass production was obtained in 2005; small-scale commercial farms were established in 2006; and the first technology transfer to the private sector began in 2008. Based on these advances, the need to optimize the production of juveniles was identified. With this objective, three larval crops obtained from natural spawning of second-generation (F2) breeders were evaluated and biologically described. Three families n = 8 each: 1.45 ± 0.21 kg, 1.33 ± 0.12 kg, and 1.28 ± 0.10 kg from an aquaculture farm were acclimatized in the laboratory until they spawned. A total of 100,000 eggs were incubated per spawning (density: 520 eggs mL-1). Larvae (90 thousand/tank) were seeded with an initial total length (TL) equal to 2.25 mm and fed with enriched rotifers, microalgae produced in helical photobioreactors, and artemia nauplii. Growth, survival, cannibalism, size variability, and deformities obtained were registered. A total of 22,837 juveniles were harvested on day 60 after spawning. During harvest, the juvenile’s total length (TL) was 57.8 ± 7.82 mm, Absolute Growth Rate (AGR) was 0.93 mm d-1, Specific Growth Rate (SGR) was 5.41% d-1, Condition Factor (K) was 1.089, average survival was 8.4 % and total eye deformities were 6.3 %. Methodologies used to obtain natural quality spawning, improvement of live food produced by photobioreactors, and separation by size were effective aspects for the larval culture of the species, although starvation in the first days of exogenous feeding, metamorphosis, and cannibalism continue to be factors affecting final survival.